NOX4-Dependent Hydrogen Peroxide Overproduction in Human Atrial Fibrillation and HL-1 Atrial Cells: Relationship to Hypertension - Zhang, Jun; Youn, Ji Youn; Kim, Antony; Ramire, Rafael; Gao, Ling; Ngo, Doan; Scovotti, Jennifer; Mahajan, Aman; Cai, Hua L. (Frontiers in Physiology, 2012)
Background/Objectives: Atrial fibrillation (AF) is the most common type of cardiac arrhythmia with patients dying frequently of stroke. In view of the unclear etiologies of AF and a potential role of oxidative stress, the present study examined cardiac reactive oxygen species production and NADPH oxidase (NOX) expression in AF patients. Methods and Results: Patients with AF were older than those without (58.8 ± 11.7 vs. 47.8 ± 19.2, p = 0.047). Whereas total O2∙- production (determined by electron spin resonance) was similar in patients with and without AF, H2O2 production was more than doubled in AF patients (149.8 ± 26.28 vs. 66.9 ± 7.14 pmol/mg/min, p = 0.0055), which correlated well with a doubling in NOX isoform 4 (NOX4) expression. AF patients with co-existing hypertension had three-fold higher H2O2 production compared to those without (239.0 ± 125.1 vs. 83.6 ± 51.3 pmol/mg/min, p = 0.003). Treatment of HL-1 atrial cells with angiotensin II, a known modulator of atrial structural remodeling, resulted in upregulation of NOX4 and H2O2 production, further implicating a potential role of NOX4 in atrial remodeling. Conclusion: Our data represent the first implication that NOX4-derived H2O2 may play an important role in the etiologies of AF.